Cognitive decline in older long-term survivors from Non-Hodgkin Lymphoma: a multicenter cross-sectional study. Issue 5 (June 2020) - La Carpia, Domenico; Liperoti, Rosa; Guglielmo, Mauro; Di Capua, Beatrice; Devizzi, Liliana Franca; Matteucci, Paola; Farina, Lucia; Fusco, Domenico; Colloca, Giuseppe; Di Pede, Patricia; Ferrara, Marianna Luciana; Hohaus, Stephan; et al.
Abstract: Objectives: To compare cognition in a group of older long-term survivors from Non-Hodgkin Lymphoma (NHL) and in a corresponding group of non-cancer controls of the same age. Functional status, polypharmacy and multimorbidity were also evaluated. Methods: A cross-sectional study was performed in a population of 63 outpatient long-term survivors from NHL, aged 65 or more and 61 non-cancer controls. Socio-demographic, clinical and functional data were collected. Cognitive function was assessed through neuropsychological tests. Results: NHL survivors showed a slightly worse functional status than controls, they were affected by more chronic conditions (3.4 vs 2.3; p  = .003) and were taking a higher number of medications (3.4 vs 2.3; p  = .03). The Mini Mental State Examination (MMSE) was not significantly different between the groups. NHL survivors performed worse than controls in executive functioning (Trail Making Test B-A 47.9 vs 32.1 p  = .04, OR for Stroop test time over 75th percentile in survivors: 2.66; CI 95% 1.04–6.61; OR for Multiple Features Target Cancellation time over 75th percentile in survivors: 2.84; CI 95% 1.10–7.31). A small, statistically significant difference was also observed in verbal memory scores between the two groups. . Conclusions: The findings of this study suggest that, compared with non-cancer controls, older survivors from NHL may have a lower cognitive performance, especially in the executive functioning and attention domains, regardless of multimorbidity and polypharmacy. Further evidence from larger samples is needed to confirm such findings and better characterize cognitive decline in NHL survivors.